Ethyl Pyruvate Ameliorates The Damage Induced by Cyclophosphamide on Adult Mice Testes - Bakhtiary, Zahra (Int J Fertil Steril, 2016)
BACKGROUND: Cyclophosphamide (CP) is a chemotherapy drug which causes deleterious effects on testicular tissue and increases free radicals in the body. The aim of this study is to investigate the protective effects of ethyl pyruvate (EP) on testicular improvement in CP treated animals. MATERIALS AND METHODS: In this experimental study, 15 male mice (6-8 weeks) were divided into 3 groups. The control group received normal saline (0.1 ml/day), intraperitoneal (IP), CP group received CP (15 mg/kg/week, IP), and the CP+EP group received EP (40 mg/kg/day, IP) plus CP. After 35 days, we assessed serum total antioxidant capacity (TAC) along with histomorphometric and histochemical analyses of the testicles. RESULTS: The mean thickness of the germinal epithelium, diameter of seminiferous tubules, and the number of Leydig cells in the CP+EP group were higher than those of the CP group (P<0.05). The number of the mast cells in the CP+EP group significantly reduced compared with the CP group (P<0.05). Alkaline phosphatase (ALP), periodic acid-schiff (PAS) positive reactions and lipid granules in cytoplasm of the Leydig cells in the CP group increased compared with the other groups (P<0.05). TAC in the CP group significantly reduced compared with the other groups (P<0.05). CONCLUSION: This study showed the ability of EP to reduce the destructive side effects of CP in the adult mice reproductive system.